Analisis Peran Divisi Business Development dalam Mendukung Pengembangan Bisnis pada PT Len Industri (Persero) - Agustin, Putri Sulistiani; Yudhanegara, Firman (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the role of the Business Development Division in supporting business development at PT Len Industri (Persero). The research employed a descriptive qualitative method, with data collected through observation during the internship program, company documentation, and literature review related to business development. Data were analyzed descriptively to provide an overview of the activities carried out by the Business Development Division in supporting the company’s objectives. The results indicate that the Business Development Division plays a strategic role in providing business insights and analyses that support corporate decision-making. The activities include brand awareness analysis, the preparation of Astha Cita branding and Pentahelix strategy studies, Business Model Canvas (BMC) analysis, Porter’s Five Forces analysis, and business potential assessment in the Maritime Surveillance System sector. These activities help the company understand market conditions, identify business opportunities, strengthen its competitive position, and formulate business development strategies in accordance with industry needs and technological developments. Therefore, the Business Development Division contributes to supporting business development and enhancing the competitiveness of PT Len Industri (Persero) through the provision of strategic information relevant to the company’s long-term sustainability.